A Dual-Labeling Probe for Super-Resolution Imaging to Detect Mitochondrial Reactive Sulfur Species in Live Cells - Hu, Maomao; Wang, Boyang; Zhang, Hongdan; Wang, Han; Li, Huixin; Zhang, Xinyu; Zhang, Jinjin; Lu, Qianrun; Fang, Guiqian; Wang, Juan; Dong, Bo (Frontiers in Pharmacology, 2022)
Background: Mitochondria are the main sites of reactive sulfur species (RSS) production in living cells. RSS in mitochondria play an important role in physiological and pathological processes of life. In this study, a dual-labeling probe that could simultaneously label the mitochondrial membrane and matrix was designed to quantitatively detect RSS of mitochondria in living cells through nano-level super-resolution imaging. Methods: Fluorescent probe CPE was designed and synthesized. The cytotoxicity of CPE was determined and the co-localization of CPE with commercial mitochondrial probe was analyzed in HeLa cells. Then the uptake patterns of CPE in HeLa cells at different temperatures and endocytosis levels were investigated. The staining characteristics of CPE under different conditions were imaged and quantitated under structured illumination microscopy. Results: A fluorescence probe CPE reacting to RSS was developed, which could simultaneously label mitochondrial membrane with green fluorescence and mitochondrial matrix with red fluorescence. CPE was able to demonstrate the mitochondrial morphology and detect the changes of RSS in mitochondria. With the increase of mitochondrial RSS contents, the light of the red matrix will be quenched. Conclusion: CPE provides a strategy for the design of probes and an attractive tool for accurate examination to changes of mitochondrial morphology and RSS in mitochondria in living cells at the nanoscale.